Fetal anemia in monochorionic twins: a review on diagnosis, management, and outcome. Issue 1 (2nd January 2023) - Tollenaar, L.S.A.; Slaghekke, F.; Middeldorp, J.M.; Lopriore, E.
ABSTRACT: Introduction: Monochorionic twins may develop fetal anemia when blood is unequally distributed via the placental vascular anastomoses. This review focuses on the causes of fetal anemia in complicated monochorionic twins and highlights the differences in management and outcome. Areas covered: Fetal anemia can occur in the context of twin anemia polycythemia sequence (TAPS), chronic twin–twin transfusion syndrome (TTTS) and acute peripartum TTTS, and in cotwins after single fetal demise. Diagnosis of fetal anemia is based on abnormal Doppler ultrasound measurements. Management options include fetoscopic laser surgery, intrauterine blood transfusion, or expectant management, depending on the type of complication and the severity of the disease. In all complications, fetal anemia may lead to perinatal mortality, neonatal morbidity, severe cerebral injury, and long-term neurodevelopmental impairment. In TAPS specifically, anemic donors may also show bilateral deafness. Expert opinion: Knowledge on the diagnosis and optimal treatment in TTTS is nowadays widespread, but caregivers often fail to distinguish TAPS from acute peripartum TTTS at birth. A full blood count including reticulocyte count is required, and placental dye injection is extremely helpful to reach the correct diagnosis and establish the optimal management.